Clinical Outcomes of Operating an Acute Palliative Care Unit at a Comprehensive Cancer Center. Issue 10 (25th October 2022) - Jung, Eun Hee; Lee, Si Won; Kim, Yu Jung; Kang, Beodeul; Suh, Koung Jin; Lee, Ju Hyun; Jeon, Esther; Kim, Dahee; Hur, Sung Soun; Lee, Ji Yun; Kim, Ji-Won; Kim, Se Hyun; et al.
Abstract : PURPOSE: Acute palliative care units (APCUs) are inpatient services in tertiary hospitals that provide intensive symptom management and assist in hospital discharge for transitions to hospice care. We aimed to analyze the clinical outcomes of operating an APCU at a comprehensive cancer center. PATIENTS AND METHODS: We retrospectively reviewed the medical records of 1, 440 consecutive patients admitted to the APCU and analyzed demographic and clinical information, discharge outcomes, symptom assessments using the Edmonton Symptom Assessment System, spiritual distress, and financial distress. RESULTS: The median age of patients was 67.0 (range, 23-97) years, and 41% were female. The most common primary cancer types were lung (21.9%), hepatopancreatobiliary (14.1%), and colorectal cancers (12.9%). The median length of stay was 8.0 days (range, 1-60 days), and 31.0% of patients died in the APCU. Death in the APCU showed a significant decrease over time, and overall inpatient death in oncology wards did not increase after APCU opening. In total, 44.7% of patients were discharged to government-certified hospice centers. The proportion of patients discharged to certified hospice centers increased from 32.2% in 2015 to 62.4% in 2018. Among 715 patients with a follow-up evaluation 1 week after admission, Edmonton Symptom Assessment System symptom scores, spiritual distress, and financial distress showed statistically significant improvements compared with the baseline symptom scores ( P < .001). This improvement was limited to patients who did not die in the APCU. CONCLUSION: Patients with advanced cancer admitted to the APCU may experience significant improvements in distressing symptoms. The majority of patients requiring transition to hospice were successfully transferred to certified hospice centers. The percentage discharged alive improved over time.